An audit of maxillofacial fractures in patients attending the Medunsa Oral Health Centre, University of Limpopo, Medunsa Campus - Singh, Avin Sunker (My University, 2009)
Aim: The aim of this retrospective study was to record the number and demographics of patients presenting with maxillofacial fractures at the Garankuwa Hospital, University of Limpopo, Medunsa Campus. In addition, the nature of these injuries and the aetiological factors involved were recorded and analysed. Materials and methods: The approach to this study was collection of data from records of patients who were treated at the Maxillofacial and Oral Surgery Department for injuries (fractures) to facial bones. All the records for the period January 2002 to December 2005 were analysed. Results: For the period (2002-2005) under review 4000 patient files were retrieved and analysed. These consisted of 1755 (43,88%) patients with mandibular or middle or upper third cranio-facial fractures who were included in this study and 2245 (56,13%) patients who had been treated as in or out patients for other oral and maxillo-facial procedures or pathology, who were excluded. The 1755 patients consisted of 232 (13.22%) females and 1519 (86.55%) males giving a male to female ratio of 6.55:1. Seventy percent of all the patients were in the age group 20-39 years with a peak frequency in the 3rd decade. The minimum age was two years and the maximum age was 88 years. A total of 2427 fractures were recorded. Of these 2077 (85.58%) occurred in the mandible where the most common sites were the angle (28.97%), the parasymphisis (17.43%) and the body (14.75%). Nearly 80% of the fractures were caused by personal assaults, 14.87% by motor vehicle accidents, 2.34% by gunshot wounds and 3.93 % by falls. Conclusion: In conclusion this study has shown that in a South African population being studied, the leading cause of fractures to the maxillofacial skeleton were interpersonal violence (assaults and gunshots) followed by motor vehicle accidents.
Keywords: maxillofacial fractures; Medunsa Health Care Centre; audit